Application of Ultrasound to the Evaluation of Rheological Properties of Raw Asian Noodles Fortified with Barley β‐Glucan. Issue 3 (5th June 2014) - Hatcher, D.W.; Salimi, A.; Daugelaite, D.; Strybulevych, A.; Scanlon, M.G.; Page, J.H.
Abstract An ultrasonic technique (1 MHz) was employed to investigate the capability of ultrasound to evaluate barley β‐glucan (BBG) supplementation (0%, 2.5% and 5%) on the mechanical properties of raw noodles. The noodles were subjected to a 20% strain using a texture analyzer in which a custom holder for ultrasonic transducers enabled stress relaxation and ultrasonic propagation to be observed over 300 s. Ultrasonic velocity and attenuation increased and decreased, respectively, with an increase in noodle BBG content. Similarly, the longitudinal storage modulus M′ increased, while the long‐time values of the longitudinal loss modulus M″ decreased, as the BBG content was increased. The stress relaxation parameter %SR20s decreased significantly, while Peleg's K1 and K2 values increased with increasing BBG content, supporting the ultrasonic findings that the noodles displayed an enhanced resistance to deformation with an increase of BBG content. The ultrasonic technique discerned changes in the mechanical behavior of functional food products. Practical Applications This research describes the use of a relatively inexpensive ultrasonic technique to discriminate and quantify desirable improvements in raw Asian white salted noodles on the basis of their fundamental rheological parameters. The test is rapid and allows the calculation of multiple parameters to highlight the texture benefits of adding BBG to noodle flour.